2018
DOI: 10.18502/jnfs.v3i4.163
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Nisin and Lysozyme on Foodborne Pathogens Listeria Monocytogenes, Staphylococcus Aureus, Salmonella Typhimurium, and Escherichia Coli at Different pH

Abstract: Background: To prevent or inhibit the growth of pathogenic microorganisms and food spoilage factors, many studies have been done by using natural preservatives. The aim of study was to investigate the effect of different concentrations of lysozyme and Nisin on the growth rate and also to determine the minimum inhibitory concentration (MIC) and minimum bactericidal cocentratiin (MBC) of these combinations on the bacteria of Escherichia coli, Staphylococcus aureus, Salmonella typhimorium and Listeria monocytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The ingredient is part of the generally recognized as safe list of the U.S. Food and Drug Administration [10] and has been used as an efficacious antimicrobial against an array of pathogens, particularly Gram-positive bacteria in various concentrations, such as 5000 IU per gram of the products [11]. While an array of studies [12][13][14][15][16][17] are available investigating effects of nisin on enhancing the efficacy of thermal and nonthermal pasteurizations, there are limited studies to discuss the efficacy of this antimicrobial under elevated hydrostatic pressure and under precise control of temperature and intrinsic (e.g., water activity, nutrients, pH) and other extrinsic (e.g., relative humidity, presence of gases, activity and presence of competitor microorganisms) factors. This is primarily due to the fact that precision in controlling and monitoring the temperature of the pressure-based treatments has been a major challenge for academic and industrial high-pressure research in the last several decades [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ingredient is part of the generally recognized as safe list of the U.S. Food and Drug Administration [10] and has been used as an efficacious antimicrobial against an array of pathogens, particularly Gram-positive bacteria in various concentrations, such as 5000 IU per gram of the products [11]. While an array of studies [12][13][14][15][16][17] are available investigating effects of nisin on enhancing the efficacy of thermal and nonthermal pasteurizations, there are limited studies to discuss the efficacy of this antimicrobial under elevated hydrostatic pressure and under precise control of temperature and intrinsic (e.g., water activity, nutrients, pH) and other extrinsic (e.g., relative humidity, presence of gases, activity and presence of competitor microorganisms) factors. This is primarily due to the fact that precision in controlling and monitoring the temperature of the pressure-based treatments has been a major challenge for academic and industrial high-pressure research in the last several decades [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the application of LYS alone had low antibacterial effect on Pseudomonas spp. due to its poor inhibitory effect on Gram-negative bacteria ( 21 , 22 ). However, the count of Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…The β-1,4 glycosidic bond between N-acetylglucosamine and N-acetylmuramic acid in the bacterial cell wall can be hydrolyzed by LYS. Therefore, LYS shows strong antibacterial activity against Gram-positive bacteria, but this ability is weaker in Gram-negative bacteria due to the protection of the cell wall by an outer membrane of the Gram-negative bacteria ( 21 , 22 ). Given that, LYS has a limited application in the aquatic products industry, but this restriction may be eliminated by combining with other preservatives that can increase its antibacterial spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted here that, in general, the combination of lysozyme with nisin to prevent food spoilage has been used by other researchers who have shown that the effect of the combination of lysozyme and nisin on S. aureus cells is more effective at pH 5.5 (MIC is 19 µg/mL) [ 47 ]. The effect of the combination of the antibiotic with the enzyme on E. coli cells was more pronounced than the effect of each of them separately, especially at pH 5.7 and 8.0.…”
Section: Enzymes In Combinations With Other Enzymes Antibiotics Nanop...mentioning
confidence: 99%